Role of 8-Oxoguanine and its repair mechanisms in paediatric medulloblastoma - Imani, Katheeja (2023)
Medulloblastoma a malignant tumour of the cerebellum constitutes around 20% of the Central Nervous System tumours occurring in children. In a recent PhD thesis, a previous student characterised the role of a multifunctional protein YB-1 (Y-Box Binding Protein 1), in paediatric medulloblastoma. A part of this work aimed to identify the transcriptional targets regulated by YB-1 under acute and chronic treatment of cisplatin and vincristine in Group 3 Medulloblastoma by performing chromatin immunoprecipitation and DNA sequencing. However, this work presented with unexpected peak enrichment in the input samples caused by 8-oxoguanine. One of the most commonly oxidized bases in the nucleotide pool, DNA and RNA is guanine and this oxidation is mutagenic as it can pair to either cytosine(C) or adenine(A). In the nucleotide pool, 8-oxoguanine can be repaired by NUDT1(Nudix Hydrolase 1) and in the DNA it is repaired by OGG1 (8-Oxoguanine DNA Glycosylase) and MUTYH (MutY DNA Glycosylase). The 8-oxoguanine in the RNA is assumed to be repaired by YB-1. 8-oxoguanine lesions detected in the ChIP sequencing data of the Group 3 medulloblastoma cell lines could have either been detected because they were already present naturally in these cell lines or they could have occurred artefactually during the ChIP sequencing assay. This study aimed to determine if the 8-oxoguanine lesions were natural or artefactual by employing immunofluorescence. With western blot analysis and immunofluorescence, single and dual staining assays the expression levels of the repair mechanisms of 8-oxoguanine, their role in regulating 8-oxoguanine levels and the extent of colocalization of YB-1 and 8-oxoguanine in group 3 primary tumour cell lines and their corresponding metastatic cell lines were analysed. Through these assays, we conclude that 8-oxoguanine lesions are naturally occurring in group 3 medulloblastomas despite the repair mechanisms being active. We provide evidence that YB-1 is involved in regulating the levels of 8-oxoguanine as well as shows a possibility of colocalization with 8-oxoguanine in the group 3 primary tumour cell lines and their corresponding metastatic cell lines. Thus, this study has shown that YB-1 has the ability to interact with 8-oxoguanine and further study will help establish the relationship between YB-1 and 8-oxoguanine and their involvement in paediatric medulloblastoma.